Vitellogenin expression in the oilseed rape pest Meligethes aeneus. (21st November 2017) - Kaiser, Caroline; Lazaridou, Christina; Vagn Jensen, Karl‐Martin; Labouriau, Rodrigo; Kristensen, Michael
Abstract: When investigating insecticide resistance of pest insects, for example, the pollen beetle Meligethes aeneus, it is relevant to differentiate toxicological and molecular genetic data between male and female specimens. A molecular sex determination method would allow resistance testing to be run without prior sorting of the samples. A one‐step quantitative RT‐PCR method for quantification of the yolk protein vitellogenin expression in the pollen beetle was established. The expression level of vitellogenin relative to tubulin was determined. Pollen beetles were tested at different time points during their development to determine if vitellogenin is a reliable molecular marker for detection of sexually mature females. The differentiation between females and males by relative expression of vitellogenin to tubulin is conditional regarding the life cycle. Sexually mature females and males could easily be distinguished, whereas immature specimens could not be seperated. Vitellogenin expression is a successful marker for identification of sexually mature pollen beetles. Females from the spring populations showed vitellogenin expression when the temperature was above 10.2°C. Further, detailed observations of vitellogenin throughout the spring indicated a strong relationship between daily temperatures and vitellogenin expression, which is an indicator of oviposition ability.